Utilizing ultrasonic energy for reduction of free fatty acids in crude palm oil - Hayyan, Adeeb; Mjalli, Farouq Sabri; Hayyan, Maan; Alnashef, Inas Muen; Mirghani, Mohamed Elwathig Saeed (Academic Journals, 2012)
Recently, biodiesel production from abundant bio-sources has drawn the attention of the academic and the industrial community. In this study, crude palm oil (CPO) containing 8.7% free fatty acid content (FFA) was used as raw material. Different common types of acid catalysts (sulfuric acid, methanesulfonic acid and hydrochloric acid) were optimized to investigate the catalytic activity of each acid in the pre-treatment of CPO by the esterification process. Ultrasonic energy was used for the reduction of FFA in CPO. FFA content was measured at different sonication intervals, and the optimum time was determined. Hydrochloric acid showed the highest catalytic activity in the reduction of FFA content in CPO, as well as in converting FFA to fatty acid methyl ester (FAME). From this work, it is reasonable to conclude that there is significant enhancement in the pre-treatment of oils by applying ultrasonic energy using long sonication time.